Jakość informacji sprawozdawczych w kontekście rachunkowości behawioralnej a praktyka gospodarcza - Hasik, Wojciech (The quality of reporting information in the context of behavioural accounting versus economic practice, 2008)
Financial accounting in Poland as in all countries in the Continental Europe is subject to changes that have not been observed before. Accounting paradigms (informational function prevails over the evidence function) as well as the ethos of an accountant is now changing. The created catalogue of required quantitative features defines the correctness of reporting information. The objective of the article is presentation of arguments confirming the thesis that in accounting practice it is difficult to ensure the required quantitative features. The author quotes the practical examples which prove that despite binding legal regulations, believed to be sufficient so far, there are significant obstacles disabling the reception of clear and useful reporting information.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1199, s. 20-27